Rothmund-Thomson syndrome: a case series from a tertiary pediatric hospital in Mexico - Alicia P. Sánchez-Padilla; Adriana M. Valencia-Herrera; Mirna E. Toledo-Bahena; Carlos A. Mena-Cedillos; Sonia Toussaint-Caire (Permanyer, 2022)
Background: Rothmund-Thomson syndrome, also known as congenital poikiloderma, is a rare autosomal recessive genodermatosis with onset in early childhood that affects at a multisystem level. Case reports: Case 1. A 4-year-old male patient, consanguineous parents, 26-year-old brother with a probable diagnosis of Rothmund-Thompson syndrome. He presented with adactyly of the right thumb, hypoplasia of the left thumb, delayed growth and psychomotor development. At 3 months, he presented rough, dry, sparse hair and erythematous lesions on the face, leaving hyperpigmented and hypopigmented spots with a reticulated pattern. We detected hypoacusis, skeletal alterations, narrow chin, short stature, severe malnutrition, and chronic and asymptomatic hypodontia. Genetic sequencing showed a mutation for the RECQL4 gene, for which a multidisciplinary follow-up was provided by the genetics, gastroenterology, nutrition, endocrinology, stomatology, audiology, orthopedics, rehabilitation, ophthalmology and oncology services. Case 2. A 2-year-old female patient presented facial erythema that spread to the arms and legs at 3 months; skin biopsy showed poikiloderma. She was evaluated by the endocrinology service and followed up for short stature and hypogonadism. A genetic study was not performed. Conclusions: Rothmund-Thomson syndrome is characterized by atrophy. Only a few cases are reported in the literature. We present two cases of Rothmund-Thomson syndrome, emphasizing its clinical and dermatological characteristics.